Research on Ground Subsidence Risk Assessment in the Start-up Area of Jinan - Yin Xiuzhen; Ye Lin; Liu Shuoshuo; Qu Yuanhui; Jia Chao (E3S Web of Conferences)
Ground subsidence, as a kind of slow-onset geologic disaster, has shown an expansion trend in many new urban areas in China in recent years, posing a serious threat to the safety of urban infrastructure and regional spatial development. As the core bearing platform of the National Comprehensive Pilot Zone for Conversion of Old and New Dynamics, the risk of ground subsidence has gradually emerged in the context of rapid urbanization and high-intensity resource development in the starting area of Jinan. Based on multi-source data such as geo-environmental conditions, groundwater dynamics, construction intensity, etc., this paper constructs a ground subsidence risk evaluation index system, applies the hierarchical analysis method (AHP) and the GIS spatial superposition model to carry out the risk classification, analyzes its spatial and temporal distribution characteristics and main control factors, and puts forward targeted zoning prevention and control countermeasures. The results of the study can provide decision-making support for urban planning, engineering construction and geologic disaster prevention and control in the starting area of Jinan.